How Parents Influence Deviant Behaviour among Adolescents: an Analysis of Their Family Life, Their Community and Their Peers - Nuredin ÇeÇi (Проблеми на постмодерността, 2017)
The goal of this literature review is to analyse the effect the family has on an adolescent's behaviour. It is believed that parents have direct and indirect control. Previous research has found that parents directly influence their children's behaviour through the parenting techniques utilized. Parental support is the largest influence on creating preferable behaviour in adolescents. Along with the direct influence from parents, the parents have indirect control over the community through which the adolescents lives in and socializes with peers in. Adolescents require strong bonds in their community. Through these bonds, adolescents are watched over and other families reciprocate the actions. When these conditions are not provided an up-rise in juvenile crime may overtake the community. Adolescents learn greatly from their peers. The family has an indirect control over peers through community watch and their parenting techniques; teaching the child not to succumb to peer pressure. This information is vital due to the presence of juveniles in the criminal justice system.